The Use of Dual Vacuum Stabilization Device to Reduce Kidney Motion for Stereotactic Radiotherapy Planning. (April 2015) - Pham, Daniel; Kron, Tomas; Styles, Colin; Whitaker, May; Bressel, Mathias; Foroudi, Farshad; Schneider, Michal; Devereux, Thomas; Dang, Kim; Siva, Shankar
Abdominal stereotactic ablative body radiotherapy is aided by motion management strategies to ensure accurate dose delivery as targets such as the kidney are easily influenced by breathing motion. Commercial devices such as compression plates and dual vacuum technology have been demonstrated to reduce the motion of lung and liver tumors. The aim of this study was to evaluate the effectiveness of a dual vacuum system in reducing kidney motion as well to investigate any relationship between abdominal wall motions with kidney motion. Ten healthy volunteers were set up with and without vacuum compression (Elekta BodyFIX TM ) to simulate free and dampened breathing. Ultrasound imaging was used to visualize kidney motion at the same time an abdominal surface marker was monitored using infrared imaging (Varian, Real Time Position Management). The resulting kidney and abdominal motion tracks were imported into motion analysis (Physmo TM ) and custom built software (Matlab) to calculate amplitude of motion independent of shifting baselines. Thirty-four kidney datasets were available for analysis, with six datasets unable to be retrieved. With vacuum compression six out of nine participants showed a mean reduction of kidney motion ranging between 1.6 and 8 mm ( p < 0.050). One participant showed an increase in motion of 8.2 mm ( p < 0.001) with vacuum compression. Two participants showed no significant change (<1 mm) in kidney motion. No relationship was observed for abdominal wall motion and motion changes in the left kidney ( r = 0.345, p = 0.402) or right kidney ( r = 0.527, p = 0.145). Vacuum compression reduced kidney motion in the majority of participants; however larger breathing motion can also result from its use. No pattern emerged regarding which patients may benefit from vacuum immobilization as abdominal wall motion was not found to be an adequate surrogate for kidney motion.